Sustained effectiveness of weekly iron-folic acid supplementation and regular deworming over 6 years in women in rural Vietnam. - Gerard J Casey; Ta T Tinh; Nong T Tien; Sarah Hanieh; Luca T Cavalli-Sforza; Antonio Montresor; Beverley-Ann Biggs (PLoS Neglected Tropical Diseases)
Background Weekly iron-folic acid (IFA) supplementation and regular deworming is effective for the prevention of iron deficiency and anaemia in women of child-bearing age. Between 2006 and 2013, a program of weekly IFA and biannual deworming was implemented in Yen Bai province, Vietnam. In this study we aimed to determine the effectiveness of the program in reducing anaemia and the prevalence of hookworm infection after 72 months (six years). Methods This prospective cohort study followed up a cohort of 389 women of child-bearing age from baseline until six years after the introduction of the weekly IFA (one tablet containing 200 mg ferrous sulphate, 0.4mg folic acid) and deworming (one 400mg tablet of albendazole given twice yearly) program (May 2006 to 2012). In each of the six surveys (baseline and five follow-up surveys) we measured haemoglobin and ferritin, and the burden of soil transmitted helminth (STH) infections, and in the 72 month survey we also administered a questionnaire to assess adherence and possible impediments to participating in the program. Results Two hundred and fifty six (65.8%) of the original 389 women enrolled in the cohort attended the final 72 month survey. Haemoglobin levels were 122 g/L [95% C.I. 120, 124] at baseline and increased to 135g/L [95% C.I. 133, 138] after 72 months. The prevalence of anaemia was 37.8% [95% C.I. 31.0, 44.7] at baseline and reduced to 14.3% [95% C.I. 9.5, 19.1]. Hookworm infection prevalence, 75.9% [95% C.I. 68.1, 83.8] at baseline, reduced to 10.2% [95% C.I. 5.4, 15.0] with no moderate or heavy intensity infections. Seventy-two percent of participants reported still taking at least 75% of the weekly supplements, and 85.0% had taken the most recent deworming treatment. Discussion Anaemia rates fell significantly during the six-year program, and STH infections were eliminated as a public health risk. Adherence was well maintained but long-term sustainability is challenging in the absence of ongoing external support.